COMPARISON OF CPR TRAINING WITH MOBILE APPLICATION AND SIMULATION TO KNOWLEDGE AND SKILL OF CPR - Rismawan Adi Yunanto; Titin Andri Wihastuti; Septi Dewi Rachmawati (NurseLine Journal, 2017)
Out-of-Hospital Cardiac Arrest (OHCA) is the focus of global health problems with high mortality rate. The delay of reporting and giving a quick CPR are the common causes of the problem. The solution that can be done is to provide CPR training in the community to form a CPR bystander who can provide CPR to the victim. This study aimed to analyze the comparison of CPR training based on mobile application and simulation to the knowledge and skill of CPR. This research was quasi experimental with pretest-posttest design. Fifty respondents were divided into two groups: mobile application and simulation. Respondents were determined by purposive sampling technique. Data were collected using questionnaires and observation sheets. Data were analyzed using dependent t test and independent t test. The result of dependent t test showed that mobile application group had a significant influence on increasing the knowledge (p = 0.000) and the skill (p = 0.000) of CPR. The simulation group also showed the same result. Independent t test showed that there was a significant difference of knowledge between mobile application and simulation. Mobile application had greater score than simulation group (p=0.021). There were also significant differences between mobile application group and simulation group in skill of CPR. The simulation group had greater score of CPR’s skill than mobile application group (p=0.044). The result shows that CPR training using mobile application can give bigger influence on increasing the knowledge, while simulation method can give bigger influence on increasing the skill in doing CPR.